A survey of the name, title, and series authority control practices of university libraries in Metro Manila - Moldes, Sylvan Dan M. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
The study determined the practices of university libraries around Metro Manila on name, title, and series authority control. Purposive sampling was employed to select the respondents. Six weeks was alloted for the data gathering that used questionnaires as primary research instrument. A total of 20 respondents from different university libraries participated. From the data, it was found that 80% of the respondents practice authority control, while 20% do not. Across all forms of authority control tackled in this study, monographs emerged as the type of material most controlled. Additionally, personal names are the most common type of name controlled. More than half of the respondents perform a combination of in-house and outsourced authority control work, wherein the authority file is actively integrated with the online catalog. The results confirm the existing literature that personal names tend to be the most controlled type of name. However, while most of the literature focused on the practice of name authority control, this research further extended those by including title and series authority control. Sources of verification of authorities and the library employees concerned with authority control were also discussed.